2009
DOI: 10.1177/1933719109337260
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Protein Deprivation: Changes in Systemic Renin-Angiotensin System of the Mouse Fetus

Abstract: We tested the hypothesis that maternal protein deprivation during gestation results in changes in expression of the systemic renin-angiotensin system in fetal mice. Fetal weight was decreased significantly as a consequence of 50% maternal protein deprivation during second half of gestation. In fetal liver, angiotensinogen protein expression was reduced significantly despite a significant increase in messenger RNA (mRNA). In fetal kidneys, both mRNA and protein levels of renin were increased significantly. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 39 publications
2
34
0
Order By: Relevance
“…The real-time PCR method is described in detail elsewhere (11,12). Briefly, we used an Allprep DNA/RNA mini kit (catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…The real-time PCR method is described in detail elsewhere (11,12). Briefly, we used an Allprep DNA/RNA mini kit (catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…Hypertension (Bogdarina et al 2007, Goyal et al 2009, type 2 diabetes mellitus (Williams et al 2008), cancer (Schmutte & Jones 1998), neurodegenerative disorders (Obeid et al 2009) to altered DNA methylation. In the antenatal proteindeprived mouse fetus, we observed hypomethylation (activation) of the promoter region of the angiotensin-I-converting enzyme (ACE) and increased ACE mRNA expression in the lung and brain (Goyal et al 2010(Goyal et al , 2011a.…”
Section: Dna Methylation and Dohadmentioning
confidence: 99%
“…Goyal et al observed a decreased number of nephrons and onset of hypertension in a mouse model treated with an angiotensin receptor blocker and suggested that RAS plays a key role in kidney growth and maturation. 25 Grigore et al feed neonatal mice with a high dose of the angiotensin receptor inhibitor losartan and found that all mice became hypertensive by the age of 22 weeks and the number of nephrons was decreased by at least 42%, which indicated that insufficient angiotensin activity will disrupt normal kidney development and result in a decreased number of nephrons. 26 In humans, Moritz et al observed that cells containing renin were located in the deep cortex and suggested that both the lack of nutrients in the uterine environment and inhibition of RAS activity resulted from kidney impairment, and the limited supply of nutrients and oxygen inhibited RAS expression.…”
Section: Discussionmentioning
confidence: 99%